ASSESSMENT OF THE NEED FOR VEGETABLES IN ACCORDANCE WITH RATIONAL NORMS OF CONSUMPTION - A. A. Lushchik (Овощи России, 2019)
Problems of proper nutrition and health of citizens are becoming increasingly important every year. A significant number of chronic non-communicable diseases have been observed in Russia and its regions for several years. Thus, according to the Territorial body of the Federal state statistics service for the Irkutsk region in 2017, the mortality rate from diseases of the circulatory system was 615 people per 100 thousand people, 218 people per 100 thousand people died from neoplasms. The reason for the increase in the incidence of population researchers believe the change in socio-economic structure, lifestyle and diet. At the same time, the President of the Russian Federation defined the task of achieving the average life expectancy of Russians at the level of 78 years in the may Decree of 2018. Currently, for the Irkutsk region, this figure is at the level of only 69 years and at the current rate of growth by 2024 will reach only 75 years. In this regard, we need a set of measures aimed at improving the health, living and working conditions of citizens of the country, which can be implemented, including through ensuring a normal diet of life and consumption of basic products, including vegetables, at a level not lower than the rational norms of their consumption. The article presents an assessment of the capacity and potential of the market of vegetable products on the materials of the Irkutsk region, the main producers, exporters, importers of vegetables, the forecast of shortage of vegetables. Social efficiency in achieving the proposed performance indicators will be determined by increasing the life expectancy of the population, reducing morbidity, improving the quality of life of those suffering from diseases associated with malnutrition, and the ratio of the obtained favorable social results to the costs to achieve them. Economic efficiency will be expressed by assessing the impact of the results achieved in the framework of program activities on the formation of the gross product, ensuring the dynamics of economic growth and increasing productivity, as stated in the presidential decree and Federal national projects until 2024. The practical application of vegetable demand calculations in accordance with rational consumption norms can be used in the process of marketing research to identify the potential market entry of new players or increase the production of fresh vegetables by their existing producers.